2013
DOI: 10.1186/1471-2458-13-923
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of overweight and obesity in expectant parents: socio-demographic patterns and within-couple associations

Abstract: BackgroundOverweight and obesity in pregnancy increase the risk of several adverse pregnancy outcomes. However, both mothers’ and fathers’ health play an important role for long-term health outcomes in offspring. While aspects of health and lifestyle of pregnant women have been reported, the health of expectant fathers and correlations of health variables within couples have received less attention. This study aimed to explore the prevalence and socio-demographic patterns of overweight and obesity in Swedish e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 70 publications
2
17
1
Order By: Relevance
“…In line with other Swedish studies [ 12 , 15 , 16 , 29 ], an urban–rural gradient of overweight and obesity was observed among pregnant women independently of educational level. The sample size in the present study allowed for a more detailed categorisation of residential area than the often used urban/rural classification.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with other Swedish studies [ 12 , 15 , 16 , 29 ], an urban–rural gradient of overweight and obesity was observed among pregnant women independently of educational level. The sample size in the present study allowed for a more detailed categorisation of residential area than the often used urban/rural classification.…”
Section: Discussionsupporting
confidence: 91%
“…It is well known that individuals with lower education and socioeconomic position are more often overweight or obese in comparison to people with higher education or socioeconomic position. This social inequality is also observed in pregnant women [ 5 , 12 , 13 ]. A steepened social gradient has been implied in the Nordic countries but the evidence for increased social inequality of overweight and obesity is inconsistent [ 14 ].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…[34][35][36][37][38][39] In addition, BMI has been shown to be a critical risk factor for women's reproductive health, such as ovulation, menstruation, pregnancy, and delivery. [40][41][42][43][44] Obesity, metabolic syndrome, heart disease, and breast cancer are also factors related to early menarche and menstrual irregularity. [45][46][47] In Korea, height was positively related and waist circumference was inversely related to a menarche age of 16 to 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in nutritional consumption, physical activity and meal and smoking patterns are likely to be contributing causes. Earlier studies have reported the relationship of education with pre pregnancy obesity [ 29 , 30 ]; reports on socio-demographic factors associated with pre pregnancy underweight are scarce, however, possibly due to underweight not being considered a real health issue in high income countries. Women of mid and low education as well as non-western ethnic minority more frequently reported pains or other complaints, poor mobility and especially back pains, which are similar to the findings of other studies and may be associated with occupation type [ 31 ].…”
Section: Discussionmentioning
confidence: 99%